PENGUATAN PENDIDIKAN KARAKTER RELIGIUS MELALUI PROGRAM CENDIKIA KARAKTER DI SMP IT CENDIKIA QURANI ARJASARI BANDUNG - Usep Saepuloh; Yana Mulyana; Muhammad Aditya Firdaus (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Efforts to improve religious character in students are important things to be taught and instilled from an early age to answer various problems of the nation. There are various programs that can to do by the school in facilitating the improvement of religious character for students, one of which is through the Character Scholars program. This study aims to describe efforts to increase religious character through the Character Cendikia program at SMP IT Cendikia Qurani Arjasari, with qualitative methods for data collection carried out by researchers including observation, interviews, and documentation. The data analysis carried out was triangulation. The results of the study show that the Character Cendikia program has several programs, namely daily programs, weekly programs, monthly programs, and semester programs. The program succeeded in instilling religious character values in students. With an Islamic background, this school forms an environment that supports the formation of religious character. With a variety of activities such as Duha prayer, memorizing the quran, field practice and others, it becomes a good habit for students. The method used in instilling character by this school is in line with the opinion of experts, such as methods 1) teaching 2) exemplary 3) habituation 4) motivation 5) enforcing the rules.